The Limestone Massif of Estremadura - Rodrigues, Maria Luísa (2021)
The karst landscapes of Portugal are confined to the sedimentary basins where there are uplifted limestone rocks. The most important limestone massif is the Limestone Massif of Estremadura (LME) located in the Western Sedimentary Basin that contact by an overthrust fault with the active Tagus River sedimentary basin. Although there are other limestone massifs in Portugal, they are smaller and have less developed karst landforms. What makes the LME special is the thickness of the limestone, its high content of calcium carbonate and tectonic uplift of the entire massif in relation to the surrounding areas. No permanent river cuts across the limestone mass, and the water circulation is subterranean. For this reason, most of great karst springs are located along the LME borders, principally in the eastern side, near the tectonic contact with the impermeable sediments of the Tagus Basin. In this chapter, the main geomorphological units within the LME are characterized: three anticline mountains, two plateaus and three tectonic depressions in graben structures. Examples of the main types of karst landforms according to dimension are presented, namely: large karst landforms (poljes, big uvalas, karst canyons or amphitheatre head valleys), medium karst landforms (dolines, dry valleys, karst springs or waterfalls) and small karst landforms (karren features or swallow holes). Among this set of karst landforms, some show a particular value and should be preserved as geoheritage and geomorphosites. Two cases are the polje of Minde and the Fórnia amphitheatre head valley that contains valuable remnants of relict slope deposits from Quaternary cold periods.